The "animalization" influence on the specific activity of a live plague vaccine in the model animal experiments - Tatyana Ponomarevа (National Scientific Medical Center, 2016)
Objective: Assessment of the "animalization" impact on the immunogenicity and viability of EV live plague vaccine. Methods: In this research we have used a vaccine strain of Yersinia pestis EV (a RIEH line), and a strain 231 from the National Depository of highly dangerous microorganisms of the Kazakh Scientific Center of Quarantine and Zoonotic Diseases (KSCQZD). For the cultivation and evaluation of cultural, biochemical properties, as well as phage lysability of the vaccine strain we used Hottinger agar, Hottinger broth, peptone water with 1% glycerol, 1% sucrose, 1% lactose, 1% rhamnose and Andred indicator, a sterile 0.9% sodium chloride, and also plague diagnostic bacteriophages L-413 and Pokrovsky, produced in KSCQZD, and determination of the cell concentration using 10 units standard turbidity. We carried out "animalization" of the vaccine by its intravenous infusion to 5 rabbits weighting from 2 to 2.5 kg, with subsequent (after 3-4 hours) isolation of the vaccine strain culture from rabbit's internal organs. We evaluated the protective activity in acute experiments of contamination of previously immunized guinea pigs weighing from 250 to 350 g (by a number of survived animals), and immunogenicity by ED50 value for all series of "animalized" and "not animalized" EV vaccine. The viability (percent of live cells) was determined by the number of colonies grown on Hottinger agar compared with the concentration of bacteria marked on an ampoule. As the percentage of viable microbial cells in a series, we accepted the arithmetic mean calculated for the three ampoules of the same series. Results: Indicators of the specific activity of the vaccine series prepared with the inclusion in the process of an "animalization" stage showed their significant growth. Significant increase in the number of surviving after contamination guinea pigs in combination with a significant reduction ED50 indicates that short stay of the vaccine strain in a rabbit body leads to a significant increase in protective activity (immunogenicity) of the finished vaccine. The number of viable cells in the final vaccine increases, too. Conclusions: Short-term (within 3-4 hours) stay of the 2nd generation culture during the process of a live plague vaccine production greatly enhances its immunogenicity (protective activity). The vaccine obtained with the inclusion in its production process of the "animalization" step contains a significantly greater number of viable microbes, as compared to conventional technology without "animalization".